Pandemic to Endemic: Changing Learning Styles as Coping Mechanism - Kamal, Nurmala Mustaffa; Mohamed, Mahfudzah; Ismail, Puteh Mariam; Ahmad, Asyaari Elmiza; Rahim, Roslina Abdul (Journal of Accounting, Business and Management (JABM), 2024)
Professional accountancy students face challenges as examinations are conducted by professional bodies separate from their learning institutions. As COVID19 enters the endemic stage, the transition from online distance learning (ODL) back to traditional face-to-face learning raises learning behaviours and preferences issues. This quantitative research on professional accounting students at Universiti Teknologi Mara (UiTM), aims to provide a perspective and critical evaluation of students' learning preferences and its implications on the appropriate teaching and learning pedagogy. The Partial Least Square Structural Equation Modelling (PLS-SEM), a multivariate method, is used to find path models with latent constructs to identify the influencing factors of ACCA students’ examination performances. It is found that ODL classes do not significantly change students’ learning style. It can be deduced that students are comfortable with ODL and traditional classes. Generally, the learning profile of the student population in this study indicates that the ability to adapt is still lacking and this may be a localised scenario. In Malaysia, to address this may require a comprehensive review of the education system that can develop students to become independent and active learners with high self-motivation.